STUDI OPTIMASI EKSTRAKSI KANDUNGAN SENYAWA FENOLIK TOTAL DAN UJI AKTIVITAS ANTIOKSIDAN DARI DAUN MANGGIS (Garcinia mangostana Linn.) - Salim, Emil; Afritunando, Yogi; Febriana, Nindi Antika; Efdi, Mai (Jurnal Riset Kimia, 2019)
This study aims to determine antioxidant activity and total phenolic content of mangosteen leaves in several different solvents. The antioxidant activity test of the extract was determined by the DPPH method and the total phenolic content was determined by the Folin-Ciocalteu method. The phytochemical test of mangosteen leaves showed the presence of phenolic compounds, saponins, triterpenoids and alkaloids. The extraction results increase with increasing water content in methanol, ethanol and acetone. The highest amount of extract was obtained using 50% acetone solvent (34.98 Â± 0.17%). Extraction using 100% ethanol showed the highest total phenolic content (614.25 Â± 5.58 mg GAE / g extract) and the lowest IC50 value (5.81 mg / L). The results of this study indicate that the use of 50% acetone solvent can optimize the amount of extract and 100% ethanol can optimize the content of total phenolic compounds and antioxidant activity of mangosteen leaves.